Image-Guided Nanoparticle-Based siRNA Delivery for Cancer Therapy - Kim, Yong-Dong; Park, Tae-Eun; Singh, Bijay; Maharjan, Sushila; Cho, Kye-Soo; Pyo Park, Kyoung; Choi, Yun-Jaie; B. Arote, Rohidas; Cho, Chong-Su (Current Pharmaceutical Design, 2015)
With the discovery of RNA interference technology, small-interfering RNA (siRNA) has emerged as new powerful tool for gene therapy because of its high targeting specificity and selectivity. However, one of the limitations to successful gene therapy is the inability to monitor delivery of genes and therapeutic responses at the targeted site. Hence, a combinatorial approach of gene therapy with molecular imaging has been crucial in optimizing gene therapy. Recent advances in nanotechnology have made tremendous efforts to develop multifunctional nanoparticles that contain imaging and therapeutic agents together for image-guided therapy. The nanoparticles serve as contrast agents in imaging for disease detection with simultaneous delivery of therapeutics to cure the diseases. The therapy also helps to monitor the drug accumulation and assimilation in the body, thereby facilitating the evaluation of treatment effects. Here, we present an overview of polymer and lipid-based carriers for siRNA delivery, along with imaging agents as imageguided therapy, in the treatment of breast, lung, liver, ovarian, cervical, and prostate cancers.
Keywords: gene therapy